Transportation geotechnics : proceedings of the symposium held at the Nottingham Trent University School of Property and Construction on 11 September 2003 - Frost, Matthew W. (Thomas Telford, 2003)
Aims to address the issues of geotechnical engineering, by highlighting and addressing the trends and innovative methods being used in transportation projects in the UK. This symposium also considers some of the issues that the geotechnical engineer must address in design, specification and construction, in the context of sustainability.